2022
DOI: 10.2147/dddt.s358302
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Prognostic Factors for Response to PD-1 Inhibitors in Advanced Cervical Carcinoma: A Retrospective Study

Abstract: Purpose Programmed cell death protein 1 (PD-1) inhibitors have shown a therapeutic effect in the treatment of advanced cervical cancer in clinical trials. However, the clinical characteristics associated with response remain undetermined. This study aimed to evaluate the efficacy and prognostic factors of PD-1 inhibitors in patients with advanced cervical cancer in clinical practice. Patients and Methods The study enrolled patients with recurrent or metastatic cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…After reviewing titles and abstracts, 46 studies were selected for full-text review. Finally, 19 studies that met the inclusion criteria were included in this meta-analysis ( 4 , 12 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing titles and abstracts, 46 studies were selected for full-text review. Finally, 19 studies that met the inclusion criteria were included in this meta-analysis ( 4 , 12 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…This meta-analysis included 21 trials from 19 studies, involving 2097 patients with ARMCC. Among them, there were 15 observational studies ( 4 , 12 , 13 , 15 19 , 21 , 22 , 24 , 25 , 27 29 ), one expansion cohort study ( 23 ), and three RCTs ( 14 , 20 , 26 ). All studies included at least one group that received treatment with PD-1 inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Our study showed that the combination therapy group had better survival than the combination therapy of previous studies. A previous study by Cheng et al found that the ORR and PFS of patients with advanced cervical cancer in combination with immune checkpoint inhibitors ranged from 0–65.9% and 2.9–13.8 months, respectively ( 10 ). In our study, the ORR was 44.7% and the median PFS was 10.3 months, which is consistent with the findings of Cheng et al ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Cheng et al found that the ORR and PFS of patients with advanced cervical cancer in combination with immune checkpoint inhibitors ranged from 0–65.9% and 2.9–13.8 months, respectively ( 10 ). In our study, the ORR was 44.7% and the median PFS was 10.3 months, which is consistent with the findings of Cheng et al ( 10 ). Thus, the combination of PD-1 inhibitors and chemotherapy can improve the survival of patients compared to PD-1 inhibitors or chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 102 patients with R/M CC who received treatment with the PD-1 mAb (Sintilimab/Camrelizumab) in combination with or without anti-angiogenic medicines (Apatinib) in China showed an ORR of 51.0%, a DCR of 66.7%, and a median PFS of 11.0 months. This study found that the combination of PD-1 blockade of chemotherapy and anti-angiogenic medicines successfully extended the ORR and PFS of patients with R/M CC, especially among those with squamous carcinoma, with a recurrence time >6 months ( 61 ).…”
Section: Combination Therapy For R/m CCmentioning
confidence: 92%